Variability of individuals from a population Varronia curassavica Jacq.considering volatile compounds - Moura Fernandes, Thaise Ohana; Araujo, Emanuelle Oliveira; Santos, Adson Pereira dos; Rodrigues Lopes Silva, Julio Cesar [UNESP]; Alves da Fonseca, Francine Souza; Azevedo, Alcinei Mistico; Martins, Ernane Ronie (Univ Federal Santa Maria, 2022)
Varronia curassavica is a medicinal species native to Brazil: its anti-inflammatory properties are attributed to alpha-humulene and beta-caryophyllene. This study to investigated the population variability of V. curassavica. Leaves were collected from 40 individuals of a natural population and transferred to glass flasks (2 mL). The volatiles were extracted and analyzed using static headspace gas chromatography coupled with mass spectrometry (HS GC MS). A total of 17 compounds were detected: monoterpenes (1.6% - 68%) and sesquiterpenes (25. 7% - 79.0%), including alpha-humulene and beta-caryophyllene. Multivariate analysis was performed to estimate the dissimilarity of individuals separated the compounds into four groups. Group I was characterized by the content of alpha-pinene, groups II and IV by beta-caryophyllene, and group III by beta-pinene. The abundance of alpha-humulene showed small variations; while beta-caryophyllene showed larger variations that contributed to the population variability. This is thefirst report on the chemical composition analysis of volatile compounds in V curassavica using the IIS GC MS technique.
Keywords: alpha-humulene; beta-caryophyllene; Boraginaceae; Cordia verbenacea DC; genetic resources